Enhancement of energy-storage properties in BiFeO3-based lead-free bulk ferroelectrics. Issue 12 (15th June 2022) - Tang, Hui; Hu, Yong-Cai; Chen, Xian-Yi; Jian, Xiao-Dong; Zhao, Xiao-Bo; Yao, Ying-Bang; Tao, Tao; Liang, Bo; Tang, Xin-Gui; Lu, Sheng-Guo
Abstract: Dielectric capacitors with a high power density and fast charging/discharging rate are regarded as alternatives for energy storage applications. However, lower energy storage density and efficiency are critical issues that have to be addressed for applications as energy storage capacitors. (0.7- x )BiFeO3 - 0.3BaTiO3 - x BaZn1/3 Nb2/3 O3 + 0.1 wt%MnO2 (BFO-BTO-BZNO) ceramics were prepared via the conventional solid-state reaction approach. Both the temperature dependence of dielectric constant and slim P-E hysteresis loops confirm that (BFO-BTO-BZNO) ceramics were relaxor ferroelectrics. Furthermore, the energy storage densities and efficiencies of (BFO-BTO-BZNO) were calculated based on the hysteresis loops and direct measurements of the discharged pulse currents measured at room temperature. The results indicate that the doping of BZNO can adjust the maximum and remnant polarizations of BFO-BTO based bulk ceramics, thereby affecting the energy storage properties. And the maximum energy storage density obtained was 1.61 J/cm 3 at 180 kV/cm and room temperature. Graphical abstract: Image 1